Exploring Indonesian Regional Cultures and the Integration of Local Wisdom in the Merdeka Curriculum - Nuriadi Nuriadi (Lafadz Jaya Publisher, 2023)
This article explores the integration of Indonesian regional cultures within the framework of the Merdeka Curriculum, a recent educational policy initiative aimed at enhancing students’ holistic development. Indonesia, with its rich diversity in regional traditions, languages, and values, provides a unique opportunity to embed local wisdom into the national education system. This research emphasizes how the Merdeka Curriculum supports the preservation and revitalization of regional cultures by incorporating them into the learning process. Through qualitative analysis of educational policies and regional cultural representations in curriculum design, the study identifies key opportunities and challenges in fostering cultural awareness among students. Findings indicate that the curriculum’s flexible approach offers room for local adaptations, allowing regional cultures to be presented in ways that resonate with students' identities. However, challenges remain in ensuring consistent and equitable implementation across the country. The study concludes with recommendations for enhancing the Merdeka Curriculum’s role in promoting Indonesia's cultural diversity, particularly through collaborative efforts between educators, local communities, and policymakers.